Hair Follicle Nevus Located on the Chin of an Infant: Case Report and Review of Literature. Issue 2 (March 2016) - Larson, Krista N.; O'Shea, Patrick; Zedek, Daniel C.; Morrell, Dean S.
Abstract: Hair follicle nevi are rare, benign, congenital hamartomas that usually occur in the distribution of the first brachial arch. Histopathologically, the distinction between hair follicle nevus, trichofolliculoma, and accessory tragus has recently come into question, and it may be that they are all on a spectrum of the same condition. We report the case of a 7‐day‐old boy who presented with a "tag"‐like lesion on his midline chin that had been present since birth. Biopsy of the lesion proved it to be a hair follicle nevus.